Persepsi Masyarakat terhadap Program Urban Farming - Supyandi, Dika; Pitriani, Pipit; Heryanto, Mahra Arari (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2024)
Urban farming is increasingly developing and gaining attention, especially because of its multifunctionality and positive effects on aspects of livelihoods, household food security, health, providing social space, green infrastructure, biodiversity, creating short food supply chains, and building social cohesion. However, urban farming can only be implemented successfully if people view it positively and accept it in their communities. The success of urban farming is rooted in the positive perceptions of those who live nearby, and these perceptions greatly influence individual acceptance. Thus, studying community perceptions will help in designing strategies to achieve successful adoption of urban farming. This research aims to describe and analyze the perceptions of the community implementing the program regarding the benefits of the urban farming program. The research design used is quantitative research using Rasch Modeling. The sample collection technique was a census, which came from members of the urban farming group in RW 04 Pajajaran District, Cicendo, Bandung City. The research results show that the community has benefited sufficiently from the existence of the urban farming program in their location. The community perception of the benefits of urban farming is that urban farming can keep the environment green, beautiful and productive. However, people think that urban farming cannot minimize household food consumption costs. This means, in implementing urban farming, environmental aspects are considered more dominant as benefits compared to aspects of respondent household resilience.